Make prayers to the raven a Koyukon view of the northern forest - Nelson, Richard K. (Univ. of Chicago Pr., 1983)
Portrayal of the Koyukon people and their natural surroundings based on sixteen months of living in the villages of Huslia and Hughes, Alaska between 1968 to 1972.
Keywords: Koyukon (Indiens); Koyukon (volk); Mens en natuur; Sciences naturelles - Alaska; Écologie humaine - Alaska; Koyukon Indians; Human ecology -- Alaska; Natural history -- Alaska; Volkskunde; Natur; Koyukon